Critical Study of Keynes Consumption Theory According to As-Syaibani in Al-Kasb Book - Arief, Suyoto; Handayani, Agung Lia; Wibisono, Vina Fithriana (AL-FALAH : Journal of Islamic Economics, 2023)
Purpose: The study aims to criticize the consumption theory concept of the classical economist revolutionary John Maynard Keynes, with the theory of consumption in his book Al-Kasb belonging to Asy Syaibani, a figure who contributed to the Islamic economy, and the originator of the first work classification system.Design/Method/Approach: This study uses library research with a descriptive approach. Data collection techniques are form of collecting information data through books, journals, websites, and important documents related to research.Findings: The result of this study found that Keynes argued that current disposable income has a significant impact on current consumption. According to Keynes there is a minimal consumption limitation, it is independent of one's amount of income. This indicates that even if income is zero, the level of consuming must be maintained. His theory actually contends is a rational economy that influences individual consumption, income distribution, and also goes to hinder the growth of the national economy.Originality/Values: The contribution of this study is to see how Muslim consumers can act more rationally when they want to release some of their economic consumption, increase material and spiritual satisfaction. With ifaq consumption or issuing zakat can play a significant part as an economic stabilizer among Muslims.Â Â Â